Synthesis of 2H-furo[2,3-c]pyrazole ring systems through silver(I) ion-mediated ring-closure reaction - Milišiūnaitė, Vaida; Paulavičiūtė, Rūta; Arbačiauskienė, Eglė; Martynaitis, Vytas; Holzer, Wolfgang; Šačkus, Algirdas (Beilstein Journal of Organic Chemistry, 2019)
Fused pyrazole ring systems are common structural motifs of numerous pharmaceutically important compounds. Nevertheless, access to derivatives of the aromatic 2H-furo[2,3-c]pyrazole ring system is still quite limited, and their chemistry and functional properties remain largely underexplored. The current study investigates routes to construct this system from easily accessible starting materials using metal-catalyzed reactions. A simple and efficient procedure to access the 2H-furo[2,3-c]pyrazole ring system was developed by employing the silver(I) ion-mediated ring-closure reaction of 4-alkynyl-3-hydroxy-1-phenyl-1H-pyrazoles as a key step. The required intermediate hydroxyalkynyl substrates for this reaction were prepared by a Pd-catalyzed coupling of 4-iodo-1-phenyl-1H-pyrazol-3-ol with ethyne derivatives. The structures of the obtained target compounds were unequivocally confirmed by detailed 1H, 13C and 15N NMR spectroscopic experiments, HRMS and a single-crystal X-ray diffraction analyses. This silver(I)-mediated 5-endo-dig cyclization of readily available 4-alkynyl-3-hydroxy-1H-pyrazoles can be used as an efficient method to access many novel 2,5-disubstituted 2H-furo[2,3-c]pyrazoles.
Keywords: 5-endo-dig cyclization; 2H-furo[2,3-c]pyrazole; pyrazole; silver(I) catalyst; Sonogashira coupling